Medicinal Agroecology Reviews, Case Studies, and Research Methodologies (Taylor & Francis, 2023)
agroecological systems/health, companion-planting, natural approaches + soil remediation, plant bio-active compounds, plant-based preparations, sustainable cultivation, traditional and plant derived medicines/remedies/veterinary medicine/animal homeopathy
English
Keywords: Biology, life sciences; Botany and plant sciences; Complementary and alternative medicine and therapies; Forestry and silviculture; agroecological systems/health, companion-planting, natural approaches + soil remediation, plant bio-active compounds, plant-based preparations, sustainable cultivation, traditional and plant derived medicines/remedies/veterinary medicine/animal homeopathy